Maternal effects of the English grain aphids feeding on the wheat varieties with different resistance traits - Xiang-Shun Hu (Nature Portfolio, 2018)
Abstract The maternal effects of the English grain aphid, Sitobion avenae on offspring phenotypes and performance on wheat varieties with different resistance traits were examined. We found that both conditioning wheat varieties(the host plant for over 3 months) and transition wheat varieties affected the biological parameters of aphid offspring after they were transferred between wheat varieties with different resistance traits. The conditioning varieties affected weight gain, development time (DT), and the intrinsic rate of natural increase (rm), whereas transition varieties affected the fecundity, rm, net reproductive rate, and fitness index. The conditioning and transition wheat varieties had significant interaction effects on the aphid offspring’s DT, mean relative growth rate, and fecundity. Our results showed that there was obvious maternal effects on offspring when S. avenae transferred bwteen wheat varieties with different resistance level, and the resistance traits of wheat varieties could induce an interaction between the conditioning and transition wheat varieties to influence the growth, development, reproduction, and even population dynamics of S. avenae. The conditioning varieties affected life-history traits related to individual growth and development to a greater extent, whereas transition varieties affected fecundity and population parameters more.